PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN JENIS WACANA NARASI (Penelitian Pre-Eksperimental terhadap Siswa Kelas V SDN 4 Sukamurni): PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN JENIS WACANA NARASI (Penelitian Pre-Eksperimental terhadap Siswa Kelas V SDN 4 Sukamurni) - Rahmalia, Sopia; Rohani (Bale Aksara, 2020)
This study was conducted to determine the effect of cooperative learning model Think Talk Write (TTW) in the learning of reading comprehension types of narrative discourse. This study entitled "Effects of Cooperative Learning Model Think Talk Write (TTW) Reading Comprehension Ability Of Discourse type Narrative". The purpose of this study to determine the effect of cooperative learning model Think Talk Write (TTW) in improving reading comprehension types of narrative discourse. The method used in this study is the experimental method. Data were analyzed critically by comparing pretest and posttest by using statistical test with SPSS version 20.0 for Windows. Results of research conducted, ie cooperative learning model Think Talk Write (TTW) effect in learning reading comprehension types of narrative discourse with an average of 37.3 pretest posttest while averaging 54.3. The test results of independent samples t-test on the value of the posttest showed the Sig. (2-tailed) of 0.00 (P <0.05). The conclusions of this study is cooperative learning model Think Talk Write (TTW) can improve reading comprehension of narrative discourse types of students.